Antifouling Super Water Absorbent Supramolecular Polymer Hydrogel as an Artificial Vitreous Body. Issue 11 (25th September 2018) - Wang, Hongbo; Wu, Yuanhao; Cui, Chunyan; Yang, Jianhai; Liu, Wenguang
Abstract: Recently, there has been a high expectation that high water absorbent hydrogels can be developed as an artificial vitreous body. However, the drawbacks associated with in vivo instability, biofouling, uncontrollable in situ reaction time, and injection‐induced precrosslinked fragmentation preclude their genuine use as vitreous substitutes. Here, a supramolecular binary copolymer hydrogel termed as PNAGA‐PCBAA by copolymerization of N ‐acryloyl glycinamide (NAGA) and carboxybetaine acrylamide (CBAA) is prepared. This PNAGA‐PCBAA hydrogel physically crosslinked by dual amide hydrogen bonds of NAGA exhibits an ultralow solid content (1.6, 98.4 wt% water content), and shear‐thinning behavior, body temperature extrudability/self‐healability, rapid network recoverability, and very close key parameters (modulus, antifouling/antifibrosis, light transmittance, refractive index, ultrastability) to human vitreous body. It is demonstrated that the hydrogel can be readily injected by a 22G needle into the rabbits' eyes where the gelling network is rapidly recovered. After 16 weeks postoperation, the hydrogel acts as a very stable vitreous substitute without affecting the structure of soft tissues in eye, or eliciting adverse effects. This supramolecular binary copolymer hydrogel finds a broad application in ophthalmic fields as not only a self‐recoverable permanent vitreous substitute, but also transient intraocular filling for prevention of inner tissues in postsurgical eyes. Abstract : A supramolecular binary copolymer (SBCP) hydrogel comprising reversible hydrogen bonding crosslinks and zwitterionic segments is synthesized. This high water absorbent SBCP hydrogel, with a very low solid content (1.6 wt%), shear‐thinning behavior, body temperature extrudability/self‐healability, rapid network recoverability, excellent antifouling/antifibrosis, and key parameters closely resembling human vitreous body, functions as an ideal vitreous substitute without eliciting adverse effects.